Human Rights Education Theory of Change for Learners: Value and Awareness-Socialization Plus Model - Kranrattanasuit, Naparat; Sumarlan, Yanuar; Navasiritanaroj, Manasada (Journal of Human Rights and Peace Studies, 2022)
Teaching human rights can raise awareness of fundamental human rights and freedom of students and others. However, the ultimate teaching goal may appear in the Value and Awareness-Socialization Model and the Activism-Transformation Model to decrease human rights violations and transform students into social change agents. This paper investigates the gaps between the contents of international laws and those of Thai national laws on Human Rights Education (HRE). This paper also explores how lecturers apply the HRE models in their human rights education courses to transform their students to be a part of social change. Apart from the literature review on HRE, this paper applies the narrative research approach and semi-structured interviews collected from students to explore the features of the HRE Course. The findings reveal that the Thai laws and policies on HRE are compliant with international human rights standards. Teaching the HRE Course reveals the areas for the model’s improvement because its strategy for decreasing the tendency to violate human rights can not produce students as social change agents. Therefore, this paper proposes the Value and Awareness-Socialization Plus Model (the mixture of the abovementioned Models) to mitigate human rights violations and create social change agents.